Nuclear landscape of HIV-1 infection and integration - Lusic, Marina; Siliciano, Robert F. (Nature reviews. Microbiology, 2017)
To complete its life cycle, HIV-1 enters the nucleus of the host cell as reverse-transcribed viral DNA. The nucleus is a complex environment, in which chromatin is organized to support different structural and functional aspects of cell physiology. As such, it represents a challenge for an incoming viral genome, which needs to be integrated into cellular DNA to ensure productive infection. Integration of the viral genome into host DNA depends on the enzymatic activity of HIV-1 integrase and involves different cellular factors that influence the selection of integration sites. The selection of integration site has functional consequences for viral transcription, which usually follows the integration event. However, in resting CD4+ T cells, the viral genome can be silenced for long periods of time, which leads to the generation of a latent reservoir of quiescent integrated HIV-1 DNA. Integration represents the only nuclear event in the viral life cycle that can be pharmacologically targeted with current therapies, and the aspects that connect HIV-1 nuclear entry to HIV-1 integration and viral transcription are only beginning to be elucidated.